Efficacy of alternative and biological insecticides on Sitophilus zeamais (Coleoptera: Curculionidae) in corn grains - Bellon, Patrícia Paula; Cemin, Marina Ferreira Rosa (Seven Editora, 2023)
The study aimed to evaluate the efficiency of alternative and biological insecticides on the population of Sitophilus zeamais in corn grains. The research was conducted in a completely randomized design, containing five treatments, diatomaceous earth (750 g/t), neem oil (10 ml/L), Beauveria bassiana (20 g/L) and smoke (10 ml/L), and nine replicates, each assay consisting of 20 adults. To evaluate the insecticidal activity, samples of corn grains were placed in plastic pots submitted to treatments. The insecticides were sprinkled and sprayed on the corn grains and later, each sample was infested with 20 adults of Sitophilus zeamais, unsexed, aged between 10 and 15 days. Insect mortality was evaluated at 48, 96, 144 and 240 h after application. The total mortality of the insects was corrected by the formula of Schneider Orelli. Afterwards, the data were submitted to the nonparametric Kruskal-Wallis test at a significance level of 5%. With significant differences between treatments, the medians were compared by Dunn's test at 5% probability of error. Only the insecticide diatomaceous earth showed a significant effect on the mortality of Sitophilus zeamais for the third day (5.56%) and the sixth day (84.21%) of exposure of the product. The treatments neem, smoke and Beauveria bassiana, did not interfere in the mortality of the insect, not differing statistically from the control in any of the evaluation dates. The diatomaceous earth product showed higher efficiency on Sitophilus zeamais, reaching a percentage of 89.77% of mortality on insects. DOI:https://doi.org/10.56238/Connexpemultidisdevolpfut-118